tính giá trị của biểu thức
a) A= x5 - 15x4 + 16x3 - 29x2 +13x tại x = 4
b) B= x14 - 10x13 + 10x12 - 10x11 + ..... + 10x2 - 10x +10 tại x=9
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) Ta có:
(x+y+z)(x-y-z) = x^2 -xy -xz +yx- y^2 -yz+zx -zy -z^2
=x^2 - y^2 - 2yz - z^2.
b) Ta có: (x-y+z)(x+y+z) = x^2 +xy+xz -yx-y^2 -yz +zx+zy +z^2
=x^2 +2xz- y^2 +z^2.
c) Ta có: -16 + (x-3)^2 = -16 + ( x^2-6x+9)
= -16 + x^2 - 6x + 9
= x^2 - 6x - 7.
\(a,\left(x+y+z\right)\left(x-y-z\right)\)
\(=x\left(x-y-z\right)+y\left(x-y-z\right)+z\left(x-y-z\right)\)
\(=x^2-xy-xz+xy-y^2-yz+xz-yz-z^2\)
\(=x^2-y^2-2yz-z^2\)
\(b,\left(x-y+z\right)\left(x+y+z\right)\)
\(=x\left(x+y+z\right)-y\left(x+y+z\right)+z\left(x+y+z\right)\)
\(=x^2+xy+xz-xy-y^2-yz+xz+yz+z^2\)
\(=x^2+2xz-y^2+z^2\)
\(c,-16+\left(x-3\right)^2\)
\(=-16+x^2-6x+9\)
\(=x^2-6x-7\)
\(a,x^2-2x=24\)
\(x^2-2x-24=0\)
\(x^2-2x+1-25=0\)
\(\left(x-1\right)^2=5^2=\left(-5\right)^2\)
\(x-1=5\) hoặc \(x-1=-5\)
\(\Rightarrow\hept{\begin{cases}x=6\\x=-4\end{cases}}\)
\(b,\left(2x-1\right)^2+\left(x+3\right)^2-5\left(x+7\right)\left(x-7\right)=0\)
\(4x^2-4x+1+x^2+6x+9-5\left(x^2-49\right)=0\)
\(4x^2-4x+1+x^2+6x+9-5x^2+245=0\)
\(2x+255=0\)
\(2x=-255\)
\(x=-\frac{255}{2}\)
a/ \(x^2-2x=24\)
<=> \(x^2-2x+1-1=24\)
<=> \(\left(x-1\right)^2=25\)
<=> \(\orbr{\begin{cases}x-1=25\\x-1=-25\end{cases}}\)<=> \(\orbr{\begin{cases}x=26\\x=-24\end{cases}}\)
b/ \(\left(2x-1\right)^2+\left(x+3\right)^2-5\left(x+7\right)\left(x-7\right)=0\)
<=> \(4x^2-4x+1+x^2+6x+9-5\left(x^2-49\right)=0\)
<=> \(4x^2-4x+1+x^2+6x+9-5x^2+245=0\)
<=> \(2x+255=0\)
<=> \(2x=-255\)
<=> \(x=-\frac{255}{2}\)
a) Ta có: \(A=x^5-15x^4+16x^3-29x^2+13x\)
\(=\left(x^5-14x^4\right)-\left(x^4-14x^3\right)+\left(2x^3-28x^2\right)-\left(x^2-14x\right)-x\)
\(=x^4\left(x-14\right)-x^3\left(x-14\right)+2x^2\left(x-14\right)-x\left(x-14\right)-x\)
\(=\left(x-14\right)\left(x^4-x^3+2x^2-x\right)-x\)(thay x = 14)
\(=-x=-14\)
Vậy A = -14.
b) Ta có: \(B=x^{14}-10x^3+10x^{12}-10x^{11}+...+10x^2-10x+10\) tại x = 9.
\(\cdot x=9\Rightarrow10=x+1\)
\(\Rightarrow B=x^{14}-\left(x+1\right)x^{13}+\left(x+1\right)x^{12}-\left(x+1\right)x^{11}+...+\left(x+1\right)x^2-\left(x+1\right)x+10\)
\(=x^{14}-x^{14}-x^{13}+x^{13}+x^{12}-x^{13}-x^{12}+...+x^3+x^2-x^2-x+10\)
\(=-x-10=-9-10=-19.\)
Vậy B = -19.
a) Ta có:
\(A=x^5-15x^4+16x^3-29x^2+13x\)
\(=\left(x^5-14x^4\right)-\left(x^4-14x^3\right)+\left(2x^3-28x^2\right)-\left(x^2-14x\right)-x\)
\(=x^4\left(x-14\right)-x^3\left(x-14\right)+2x^2\left(x-14\right)-x\left(x-14\right)-x\)
\(=\left(x-14\right)\left(x^4-x^3+2x^2-x\right)-x\)(thay \(x=14\))
\(=-x=-14\)
Vậy \(A=-14\)
b) Ta có:
\(B=x^{14}-10x^3+10x^{12}-10x^{11}+...+10x^2-10x+10\)tại \(x=9\)
\(x=9\Rightarrow10=x+1\)
\(\Rightarrow B=x^{14}-\left(x+1\right)x^{13}+\left(x+1\right)x^{12}-\left(x+1\right)x^{11}+...+\left(x+1\right)x^2-\left(x+1\right)x+10\)
\(=x^{14}-x^{14}-x^{13}+x^{13}+x^{12}-x^{13}-x^{12}+...+x^3+x^2-x^2-x+10\)
\(=-x-10=-9-10=-19\)
Vậy \(B=-19\)